Galectin-3-integrin α5β1 phase separation disrupted by advanced glycation end-products impairs diabetic wound healing in rodents - Zhongyu Zhang; Zhengde Zhao; Xiuyi Huang; Lifang Zhou; Xin Jiang; Haoliang Wu; Chenshu Liu; Kan Huang; Jielu Wen; Yunchong Liu; Michelle C. Miller; Zihan Zhao; et al. (Nature Communications)
Abstract Diabetic foot ulcers are severe diabetic complications, and promoting impaired angiogenesis is essential for wound healing. Pro-angiogenic galectin-3 is elevated in diabetic serum and promotes systemic insulin resistance that may impair wound healing. However, the exact role of galectin-3 in the regulation of diabetic wound healing remains unclear. Here, we demonstrate that galectin-3 promotes skin wound healing and angiogenesis via binding to its receptor integrin α5β1, and enhances downstream focal adhesion kinase phosphorylation by forming a liquid-liquid phase separation with integrin α5β1. Under diabetic conditions, aberrant accumulated advanced glycation end-products bind to galectin-3, blocking its interaction with integrin α5β1 and impairing angiogenesis. Topical treatment of recombinant galectin-3 in hydrogels promotes diabetic wound healing in rodents without causing systemic insulin resistance and synergizes with insulin. This study clarifies the binding of galectin-3 to integrin α5β1, instead of advanced glycation end-products, forming phase separation to promote angiogenesis and diabetic wound healing, laying the foundation for local galectin-3 therapy to treat diabetic foot ulcers.